A Clinical Study on Thyroid Dysfunction in Pregnancy and its Effect on the Fetomaternal Outcome - Shakila Yasmin, Saba Nadeem, Aisha Javed, Najm us Sehar, Sadia Shakeel, Amna Anum (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thyroid gland is the power house of human body. It provides energy for the various biochemical processes of the body and helps to maintain basal metabolic rate. Objective: To estimate the prevalence of thyroid dysfunction in pregnancy and to evaluate the obstetric and perinatal outcomes in such pregnancies Setting: Department of Obstetrics & Gynecology, Bahawal Victoria Hospital Bahawalpur from 15 January 2021 to 15 JUNE 2021 Study Design: A Descriptive Case Series. Materials and Methods: A total of 292 cases of antenatal patients, irrespective of their period of gestation were enrolled in this study by random sampling method. Patients with multiple pregnancies and having bad obstetrical history were excluded. Detailed history and obstetrical examination, routine blood test and serum TSH were performed. These patients were followed during labour, delivery and puerperium and maternal outcome and neonatal outcomes were noted. Results: In this study we enrolled two hundreds and ninety two (292) antenatal women. Out of total 292 patients only 61 (20.9%) were nulliparous and rest of the patients were multiparous. The prevalence of thyroid dysfunction in pregnancy was 8.2%. Out of this, 2.74 % patients had sub clinical hypothyroidism (SCH). Overt hypothyroidism (OH) was seen in 2.40%, sub clinical Hyperthyroidism in 1.71% & the incidence of overt hyperthyroidism was 1.37%. Maternal complication included: abortion (5.5%), pre-eclampsia (3.4%), abruption-placentae (4.1%), preterm labour (4.5%), PPH (4.2%) and puerperal sepsis (2.8%). Neonatal outcomes included: preterm births (5.4%),LBW (5.1 %), IUGR (6.2%), still birth (4.4%), neonatal death (5.1%), low APGAR score ( <7 at 5 minutes ) (6.9%). Conclusion: Thyroid dysfunction in pregnancy, though has a low incidence, but is associated with adverse maternal and fetal complications. Thus thyroid screening should be done in antenatal period to improve fetomaternal outcome.